PENGARUH SUKU BUNGA BI, KURS DOLAR, INFLASI, DAN PDB TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI INDONESIA - Yohana Silaban; Febby Lica Gabrela Simanjuntak; Thomas Firdaus Hutahaean; Hotma Mentalita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem focuses on the fluctuations of the Indonesia Composite Index (IHSG) during the 2020–2024 period, which are influenced by macroeconomic indicators such as BI interest rates, exchange rates, inflation, and Gross Domestic Product (GDP). The main issue lies in the presence of contradictory phenomena and the impact of the pandemic on capital market stability. This study aims to analyze and empirically examine the partial and simultaneous effects of these variables on IHSG movements. This research employs a quantitative approach with a descriptive-verificative method. The data used are secondary data, including monthly BI interest rates, USD/IDR exchange rates, inflation rates, and GDP from 2020 to 2024. Data analysis techniques include classical assumption tests and multiple linear regression analysis using SPSS to evaluate the influence of independent variables on IHSG both partially and simultaneously. The results indicate that the exchange rate and GDP have a significant effect on IHSG movements during the 2020–2024 period. In contrast, BI interest rates and inflation do not show a significant partial effect in this study. Simultaneously, all macroeconomic variables have a significant influence on IHSG. GDP growth serves as a key positive signal that strengthens investor confidence and drives stock price increases. This study concludes that GDP and exchange rates are the dominant factors affecting IHSG during the observed period. It is recommended that investors carefully integrate economic growth indicators and currency stability when making investment decisions. The government should maintain GDP momentum and monetary stability, while future researchers are encouraged to include additional variables such as commodity prices to broaden the analysis of capital market dynamics.